Phosphate-solubilization mechanism and plant growth promotion activity mediated by Pantoea eucalypti isolated from Lotus tenuis rhizosphere in the Salado River Basin (Argentina) - Castagno, Luis Nazareno (2011)
To isolate and characterize phosphate-solubilizing strains from a constrained environment such as the Salado River Basin and to assess their phosphate-solubilizing mechanisms, to further selection of the most promising strains to inoculate and improve the implantation and persistence of Lotus tenuis in the most important area devoted to meat-cow production in Argentina.Fifty isolates were obtained and through BOX-PCR analysis, 17 non-redundant strains were identified. Subsequently, they were found to be related to Pantoea, Erwinia, Pseudomonas, Rhizobium and Enterobacter genera, via 16S rRNA gene sequence analysis. This was in agreement with the clusters obtained by antibiotic resistance analysis. All isolates were tested for their phosphate-solubilizing activity and selected strains were inoculated onto L. tenuis plants. The most efficient isolate, was identified as Pantoea eucalypti, a novel species in terms of plant growth-promoting rhizobacteria.The isolates obtained in this study showed a significant in vitro plant-growth promoting activity onto Lotus tenuis and the best of them solubilizes phosphate mainly via induction of the metabolism through secretion and oxidation of gluconic acid.The use of these bacteria as bioinoculants, alone or in combination with nitrogen-fixing micro-organisms, could be a sustainable practice to facilitate the nutrient supply to Lotus tenuis plants and preventing negative side-effects such as eutrophication.